Sibutramine versus Metformin: assessment of anthropometric, lipid and glycemic parameters in obese and overweight high-risk patients - Leonardo Regis Leira Pereira (São Paulo State University (UNESP), 2012)
Anthropometric, lipid and glycemic parameters were compared in obese or overweight high-risk patients. This double-blind trial included 16 obese and overweight patients who followed a standard caloriecontrolled diet and received 15mg/day sibutramine or 1700mg/day metformin over three months. The changes observed in the sibutramine and metformin groups were, respectively: body mass index -6.0% and -4.0%; abdominal circumference -7.9% and -6.6%; fatty tissue -10.5% and -1.7%; total cholesterol -2.9% and -2.8%; LDL-C -0.01% and -0.1%; HDL-C -11.0% and -6.8%; total cholesterol/ HDL-C ratio +12.0% and +4.5%; HDL-C-to-LDL-C ratio -7.2% and -0.1%; triglycerides +14.0% and +22.3%; fasting glucose +4.3% and +1.4%; insulin -10.4% and -4.9%; HOMA -8.0% and -3.9%. Although the study was conducted with only 16 patients and the drugs were taken for only three months, we can see that sibutramine-treated obese or overweight highrisk patients showed a reduction of anthropometric parameters and better control of insulin resistance.